Italian Translations of the Works of P.G.Wodehouse: an Epistemic Approach - Gabriella Valentino (2017)
This dissertation addresses the area of Translation and Humour Studies where the two disciplines overlap. My main original contribution is an Epistemic Approach to the translation process that focuses on the role that knowledge plays in the process of producing, reading and translating a written fictional text. Moreover, I propose a model for the description of the process of translation, tools to identify and evaluate items of verbally expressed humour, and a methodology to classify their renderings in translation.The study investigates the Italian translations of the works by the English humorist P. G. Wodehouse. It is based on a vast primary literature (87 books) translated into Italian (176 translations and 579 editions) for which I collected metadata, available for research in the form of an Excel spreadsheet. In the light of the Epistemic Approach, this work analyses and describes texts from the translations commissioned by 16 Italian publishers to 63 translators from 1928 to 2017.After an introductory chapter where I present my model of text activation and the Epistemic Approach to translation, the project begins with a presentation of the data I collected and an exposition of the complex publishing history of Wodehouse’s works in Italy. In the second chapter, I identify a definition of style suitable for both quantitative and qualitative interdisciplinary empirical research and apply it to systematically describe Wodehouse’s style. The third chapter presents the main theories developed in Humour Studies, the key concepts I identified to describe Wodehouse’s humour and the tools I developed to assess it. Chapter 4 and Chapter 5 show the results of the analyses I performed on numerous Italian translations and retranslations. I conclude by presenting the contributions that my approach and my findings offer to the disciplines of Translation and Humour Studies and possible future developments.